Molecular Characterization of Chicken Anaemia Virus in Layers - Kulkarni, Tejashree M.; Pawade, Mrunalini M.; Mhase, Prashant P.; Tumlam, Uma M.; Dhaygude, Vitthal S.; Kolhe, Rahul P.; Suryawanshi, Dayaram S.; Muglikar, Dushyant M. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Chicken Anaemia Virus (CAV) is one of the emerging pathogens of the poultry with its genome containing three pathologically important  gene viz.VP1, VP2 and VP3. In the present study, molecular detection and histopathological examination was carried out on 25 pooled  tissue samples collected from birds suspected of CAV from different districts of Maharashtra. From 25 pooled samples, 20 samples were  found positive for the VP3 gene with an amplicon size of 376 bp. Histopathological examination revealed the loss of stem cells in the  bone marrow and lymphocytes and RBCs in the white and red pulp of spleen. Liver and kidney showed degenerative changes. The  VP3 gene confirmed tissue samples were used for chicken embryo inoculation. For virus inoculation, 07 days old embryonated chicken  eggs were inoculated with viral inoculum via yolk sac route. The inoculated eggs were incubated at 37⁰C for 10 days. The eggs were  harvested after 10 days and confirmed with PCR which revealed VP3 positive results.
Keywords: Chicken Anaemia Virus; Chicken embryo inoculation; Molecular detection